PENINGKATAN KOMPETENSI PEDAGOGIK GURU DALAM MENYUSUN PERANGKAT PEMBELAJARAN MELALUI WORKSHOP KKG MINI DI SDN SEPANDE KECAMATAN CANDI KABUPATEN SIDOARJO - Anis Mufidah (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2019)
This research is motivated by the low pedagogical competence of Sepande Elementary School teachers in developing learning tools. The reason is that learning devices are still incomplete, some teachers in compiling learning devices only copy and paste from friends and the internet. Alternative solutions to problems through the KKG Mini Workshop. The purpose of this study was to determine the increase in pedagogical competence of teachers at Sepande elementary School in the Temple District of Sidoarjo Regency in developing learning tools through the Mini KKG workshop. This study uses the PTS approach. The research subject were 10 Sepande Elementary School teachers. Data collection techniques using observation techniques, interviews, and photo documentation. The result of the study were analyzed with quantitative and qualitative techniques. The result showed the teachers pedagogical competence had increased after conducting a mini KKG workshop on the preparation of learning tools. In cycle I it was 68 (20%), in cycle II it was 74 (70%), in cycle III it was 91 (90%). This is evident that the Mini KKG workshop can improve the pedagogical competence of Sepande elementary school teachers in developing learning tools.